Control System Implementation for the IASA Microtron - Barbarosou, M.; Filippas, T. A.; Gazis, E. N.; Karabarbounis, A.; Maroulis, D.; Papanicolas, C. N.; Patavalis, N.; Rahmani, H. (HNPS Advances in Nuclear Physics, 2019)
A progress report on the architectural design and implementation of the Control System for the Racetrack Microtron at the Institute of Accelerating Systems and Applications (IASA) in Athens, Greece is presented. The Control System for the IASA CW Microtron is being developed on the Experimental Physics and Industrial Control System (EPICS) environment. Since top priority for this project is the construction and commissioning of the Mcrotron's injector, emphasis is being given to the definition and refinement of the Control Architecture and its realization for the injector. The experience gained from the Control System at the injector will guide the further development of the Control System for the entire Microtron.